Analytic Calculation of Transmission Field in Homogeneously Layered Mediums Excited by EMP - Dong-yang Sun; Wei-min Bao; Xiao-ping Li (Advances in Mathematical Physics)
This paper presents an analytic derivation for the time-domain transmission across layered mediums. The transmission coefficient and attenuation coefficient are obtained in the time-domain from general electromagnetic theory. The transmission electric field can be obtained within a few seconds by convolving the coefficients with incident EMP. The results are accordant with the FDTD method, and this approach can deal with the multilayer mediums problem. The limitations of this approach are discussed in this paper.